Newly discovered gold does not distort the economy: It is not a market failure - Walter Block; William Barnett (Review of Economic Perspectives, 2020)
We wish to "quibble" with Murphy (2019). We mean this literally. That is, we are in strong and enthusiastic agreement with virtually everything he writes therein, except for one point: we think him guilty of allowing the cloven hoof of market failure into the Austrian tent. Our purpose in the present essay is to banish market failure from praxeological premises. To wit, he maintains that pure market processes such as a gold discovery can "distort" prices and interest rates, and we argue to the contrary.
Keywords: B53; E32; E42; E58; G21; 330; distortion; interest rates; market failure; prices